Production and Operations Symposium 2007
DOI: 10.2118/106849-ms
|View full text |Cite
|
Sign up to set email alerts
|

Sealing Capacity of API Connections—Theoretical and Experimental Results

Abstract: Hydraulic fracturing has become a state of the art stimulation technique. It has been proved over the years that significant production increase can be obtained by applying the right fracturing technique. Nowadays, the most advanced techniques of geothermal energy recovery systems widely use hydraulic fracturing. The following paper presents the experimental results of the tests carried out on four different compounds using the improved "grooved plate" method. The tests have showed a large va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Murtagian et al [6] observed large influence of thread compound on the evolution of leakage rates in premium connections. Temperature is known to modify seal compound properties, and to induce axial stresses that impact sealability [7][8][9]. Also, it is recognized that nature of contained fluids affects sealing behavior [10,11].…”
Section: Review Of Fe Modelling Of Leakage In Casing Connectionsmentioning
confidence: 99%
“…Murtagian et al [6] observed large influence of thread compound on the evolution of leakage rates in premium connections. Temperature is known to modify seal compound properties, and to induce axial stresses that impact sealability [7][8][9]. Also, it is recognized that nature of contained fluids affects sealing behavior [10,11].…”
Section: Review Of Fe Modelling Of Leakage In Casing Connectionsmentioning
confidence: 99%
“…Gao et al, 14 Haruyama et al, 15 and Beghini et al 16 established the seal leakage evaluation model to analyze the leakage rate of metal gaskets. Badicioiu and Teodoriu 17 studied the sealing ability of standard American Petroleum Institute (API) connectors by combining theoretical and experimental principles. Zhao et al 18 evaluated the contact stress of subsea Christmas tree connectors at a pressure of 34.5 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Sabe-se que a natureza do fluido contido afeta o desempenho do selante (API, 2002;ASSANELLI et al, 1997;ERNENS et al, 2019). Além disso, estudos verificam grande influência da temperatura, pois ocasiona modificações no comportamento reológico do composto selante, facilitando sua extrusão e, em consequência, afetando negativamente o selo (BADICIOIU;TEODORIU, 2007;MURTAGIAN et al, 2004;XIE, 2013;TAO, 2010). Adicionalmente, o composto selante diminui o desgaste e a mudança da topografia das superfície que formam o selo metalmetal no aperto, incorporando robustez ao selo (ERNENS et al, 2018(ERNENS et al, , 2019.…”
Section: Avaliação Da Estanqueidadeunclassified